An Interfacial Solar Heating Assisted Liquid Sorbent Atmospheric Water Generator. (12th July 2019) - Wang, Xueyang; Li, Xiuqiang; Liu, Guoliang; Li, Jinlei; Hu, Xiaozhen; Xu, Ning; Zhao, Wei; Zhu, Bin; Zhu, Jia
Abstract: Harvesting water from air is a promising strategy for fresh‐water production, and it is particularly desirable for areas that lack direct access to clean water. While high‐concentration liquid sorbent is well‐known for high sorption, it has not been widely used for atmospheric water collection, being primarily limited by the difficulty in desorption. Interfacial solar heating based on a salt‐resistant GO‐based aerogel is now shown to enable a high‐concentration liquid sorbent (CaCl2 50 wt % solution) based atmospheric water generator. Fresh water (2.89 kg m −2  day −1 ) can be produced at about 70 % relative humidity, with only solar energy input and energy efficiency of desorption as high as 66.9 %. This low‐cost and effective approach provides an attractive pathway to extract water from air, to relieve the thirst of arid, land‐locked, and other areas where fresh water is scarce. Abstract : Wasser aus der Luft : Grenzflächen‐Solarthermie auf Grundlage eines salzresistenten, Graphenoxid‐basierten Aerogels wird genutzt, um die Flüssigsorbens‐basierte Gewinnung von Atmosphärenwasser bei hohen Konzentrationen (CaCl2 50 Gew.‐% Lösung) durchzuführen. Süßwasser (2.89 kg m −2  Tag −1 ) kann hiermit allein durch Solarenergie bei 70 % relativer Luftfeuchte mit einer Desorptionsenergieeffizienz von bis zu 66.9 % erzeugt werden.